2021
DOI: 10.1245/s10434-021-10867-5
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Antimicrobial Prophylaxis for the Prevention of Early-Onset Pneumonia After Radical Esophageal Cancer Resection: A Retrospective Analysis of 356 Patients Undergoing Thoracoscopic Esophagectomy

Abstract: Background. Postoperative pneumonia is a common complication after esophagectomy and is associated with a high mortality rate. Although many randomized, controlled trials have been conducted on the prevention of postoperative pneumonia, little attention has been paid to the efficacy of antimicrobial prophylaxis. The purpose of this study was to investigate the impact of antimicrobial prophylaxis on the prevention of postoperative pneumonia. Methods. Data of patients with esophageal cancer who underwent thoraco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…A single-center study of lung surgery (n=445) demonstrated similar results; amoxicillin-clavulanate was associated with a lower risk of postoperative pneumonia compared with cefamandole 11 . In addition, a previous before and after study reported that ABPC/SBT could reduce pneumonia that is likely to occur on POD 2–3 after esophagectomy compared with CEZ 16 . Antimicrobial prophylaxis covering oral bacteria (both aerobic and anaerobic) may have reduced the risk of respiratory failure and complications caused by silent aspiration in the acute phase after esophagectomy.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…A single-center study of lung surgery (n=445) demonstrated similar results; amoxicillin-clavulanate was associated with a lower risk of postoperative pneumonia compared with cefamandole 11 . In addition, a previous before and after study reported that ABPC/SBT could reduce pneumonia that is likely to occur on POD 2–3 after esophagectomy compared with CEZ 16 . Antimicrobial prophylaxis covering oral bacteria (both aerobic and anaerobic) may have reduced the risk of respiratory failure and complications caused by silent aspiration in the acute phase after esophagectomy.…”
Section: Discussionmentioning
confidence: 78%
“…According to previous studies, CEZ, ABPC/SBT, second-generation cephalosporins, and CEZ plus metronidazole have been used worldwide for antimicrobial prophylaxis in esophagectomy 7,15–18,36,37 . In the absence of evidence specific to esophagectomy, the choice of agents for antimicrobial prophylaxis varied among hospitals and across study periods; consequently, the regimens depended on hospital policies or regional guidelines 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the most common are esophageal anastomotic leakage, esophageal stricture, pulmonary infection and recurrent laryngeal nerve injury. [27][28][29] The occurrence of these complications seriously affects the quality of life of patients and may lead to non-tumor death of patients. A study showed that the median survival of patients with postoperative esophageal fistula and fistula formation was only 11 and 3.63 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…treated by drugs, and airway clearance techniques(45) and hand-assisted expectoration (46) used to assist excretion.If the prognosis of patients is known early, a focus on high-risk patients could improve their prognosis. Before surgery, strengthening the optimization of respiratory function(47), the preventative use of antibiotics(48), preoperative oral care(49), and nutritional support (50) can reduce postoperative pulmonary complications of…”
mentioning
confidence: 99%